The Impact of Project-Based Collaborative and Participatory Learning Models on Student Achievement and Recognition Faculty of Computer Science Narotama University - Achmad Zakki Falani; Arasy Alimudin; Agus Sukoco; M. Ikhsan Setiawan; Sri Wiwoho Mudjanarko; Made Kamisutara; Eman Setiawan (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to determine the influence of project-based collaborative and participatory learning on student achievement and recognition, especially at the Faculty of Computer Science, University of Narotama (Unnar). Design/methodology/approach: The model is carried out by involving the Information Systems and Informatics Engineering Study Program. It analyzes the relationship between the variables associated with the learning model. Findings: The results showed a significant effect of collaborative and participatory learning on educational accomplishments and understanding. Originality/value: This paper is original Paper type: Research paper